2013
DOI: 10.11604/pamj.2013.15.23.2040
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of alcohol misuse and alcoholic liver disease among patients in the medical emergency admission service of a large urban hospital in Subsaharan Africa ; a cross sectional study

Abstract: IntroductionUganda is among the top ten consumers of alcohol worldwide though there is little data on alcohol related liver disease. We describe alcohol use, alcohol misuse, and alcoholic liver disease among adults at the emergency admission service of a large urban hospital in Uganda.MethodsAll adults who consented were prospectively evaluated for alcohol use by inquiry and alcohol misuse by the “Cutting down, Annoyance, Guilt and Eye-opener- CAGE” questionnaire. Alcohol related hepatocellular liver injury wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
3
7
0
Order By: Relevance
“…The prevalence of AST/ALT ratio >2 in this population is 11%, suggesting potential alcoholic hepatitis, 37 concordant with a previous study in Uganda in which 10% of the population was estimated to have alcoholic hepatitis, 38 and with data from Uganda's non-communicable diseases risk factor survey which estimated that almost 10% of Ugandan adults have alcohol use disorders. 39 Data from emergency attendances at the Mulago Hospital in Kampala recorded 47% who reported alcohol use, while 21% and 10% met the study definitions of alcoholic misuse and alcoholic liver disease, respectively.…”
Section: Open Accesssupporting
confidence: 90%
See 1 more Smart Citation
“…The prevalence of AST/ALT ratio >2 in this population is 11%, suggesting potential alcoholic hepatitis, 37 concordant with a previous study in Uganda in which 10% of the population was estimated to have alcoholic hepatitis, 38 and with data from Uganda's non-communicable diseases risk factor survey which estimated that almost 10% of Ugandan adults have alcohol use disorders. 39 Data from emergency attendances at the Mulago Hospital in Kampala recorded 47% who reported alcohol use, while 21% and 10% met the study definitions of alcoholic misuse and alcoholic liver disease, respectively.…”
Section: Open Accesssupporting
confidence: 90%
“…39 Data from emergency attendances at the Mulago Hospital in Kampala recorded 47% who reported alcohol use, while 21% and 10% met the study definitions of alcoholic misuse and alcoholic liver disease, respectively. 38 Our data are based on self-reported alcohol consumption so may underestimate the true extent of alcohol use. We were unable to quantify alcohol intake or the nature of the alcohol consumed: this is challenging as alcohol is often home-brewed or home-distilled from locally grown grains or fruits, and the alcohol content may vary widely; for exmaple, the alcohol content of locally produced maizebased brews and liquor in Kenya ranged from 2% to 7% and 18% to 53%, respectively.…”
Section: Open Accessmentioning
confidence: 99%
“…The prevalence of AST/ALT ratio >2 in this population is 11%, suggesting potential alcoholic hepatitis (34), concordant with a previous study in Uganda in which 10% of the population was estimated to have alcoholic hepatitis (35), and with data from Uganda’s non-communicable diseases risk factor survey which estimated that almost 10% of Ugandan adults have alcohol use disorders (36). Data from emergency attendances at Mulago Hospital in Kampala recorded 47% who reported alcohol use, while 21% and 10% met the study definitions of alcoholic misuse and alcoholic liver disease, respectively (35). Our data are based on self-reported alcohol consumption so may underestimate the true extent of alcohol use.…”
Section: Discussionsupporting
confidence: 90%
“…These finding are consistent with results from studies in other HIV clinic populations in Uganda [ 32 , 33 ], and some clinical settings in North America [ 34 ]. However, the prevalence of any alcohol consumption was relatively lower compared to studies done in the general medical settings [ 35 ] and general community populations [ 36 , 37 ] and far lower than those from fishing communities around Lake Victoria in central Uganda which reported that 62% of male and 52% of female had drank alcohol during the last month [ 38 ]. The relatively lower prevalence of alcohol use among patients in long-term HIV care, compared to the general population, may be a result of continued counseling and risk behavior change messages including reducing alcohol consumption.…”
Section: Discussionmentioning
confidence: 90%